2002
DOI: 10.1017/s0952836902001401
|View full text |Cite
|
Sign up to set email alerts
|

Radio‐tracking reveals that lesser horseshoe bats (Rhinolophus hipposideros) forage in woodland

Abstract: Over the past 50 years European populations of the lesser horseshoe bat Rhinolophus hipposideros have severely declined, probably because of the loss of foraging habitat. To date, studies of the foraging behaviour of this species have been limited as its low mass (4±8 g) precluded the use of radio-telemetry because commercially available radio-transmitters exceeded 10% of its body mass. In this study, radiotransmitters weighing < 0.35 g were built. These increased the body mass of the animals from 4.5% to 8.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
4
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(115 citation statements)
references
References 24 publications
6
91
4
1
Order By: Relevance
“…There is experience with radio-tagging small animals down to ~10·g (Naef-Daenzer et al, 2001;Bontadina et al, 2002), confirming the 5% rule for the acceptable transmitter load, at least for birds and bats. The new transmitter will allow the application of radio-telemetry to be expanded on taxa for which virtually no experience exists, for example insects and other invertebrates, and small amphibians.…”
Section: Research Implicationsmentioning
confidence: 90%
“…There is experience with radio-tagging small animals down to ~10·g (Naef-Daenzer et al, 2001;Bontadina et al, 2002), confirming the 5% rule for the acceptable transmitter load, at least for birds and bats. The new transmitter will allow the application of radio-telemetry to be expanded on taxa for which virtually no experience exists, for example insects and other invertebrates, and small amphibians.…”
Section: Research Implicationsmentioning
confidence: 90%
“…Such habitats seem to be important for other populations too (Lutz and Mu¨hletaler 1997). Recent studies conducted in Belgium (Motte and Libois 2002) and England (Bontadina et al, 2002) indicate that woodlands are important feeding grounds for Rhinolophus hipposideros. In Austria, Reiter (2002Reiter ( , 2004 showed that the colonies were surrounded by areas with higher percentages of woodland areas than sites with no horseshoe bats.…”
Section: Introductionmentioning
confidence: 99%
“…We defined a 200 m buffer zone around all locations in accordance with the average location error of radiotracking data (see 'Radiotracking' above) (Harris et al 1990, Bontadina & NaefDaenzer 1996. Core foraging areas were calculated from the 50% kernel estimate of the utilisation distribution (Worton 1989); the smoothing factor h was set to 200 m according to the same average location error (Bontadina & Naef-Daenzer 1996, Bontadina et al 2002. The first locations of emerging bats were not recorded in order not to overestimate the vicinity of the roosts.…”
Section: Foraging Habitat Selectionmentioning
confidence: 99%
“…The hair between the scapulae was trimmed and the radiotag glued to the skin with surgical cement (SkinBond ® ). The tags used did not exceed 6% of body weight and should therefore not have affected flight manoeuvrability (Aldridge & Brigham 1988, Bontadina et al 2002. The hilly area made it extremely challenging to radiotrack the fast flying bats; therefore, we invested up to 9 nights for individual observations (mean: 5 nights).…”
mentioning
confidence: 99%